Evaluating the Structure of Subjective Well-Being: Evidence From Three Large-Scale, Long-Term, National Longitudinal Studies. - Busseri, Michael A. (Personality & Social Psychology Bulletin, 2025)
To inform the tripartite structure of subjective well-being (SWB), national longitudinal studies from the United States, Germany, and Australia were used to estimate random-intercept cross-lagged panel models (RI-CLPM) in which between- and within-individual variation in life satisfaction (LS), positive affect (PA), and negative affect (NA) was examined over periods of up to two decades. The RI-CLPMs incorporated a hierarchical conceptualization in which LS, PA, and NA are indicators of a latent SWB factor and a causal systems conceptualization in which PA and NA are inputs to LS. Results from all three samples indicated substantial loadings from LS, PA, and NA on latent SWB factors between and within individuals. Cross-lagged effects were observed among all three SWB components, rather than unidirectional from PA and NA to LS. The present findings provide valuable new insights concerning the tripartite structure of SWB between and within individuals over extended periods of time.